Combustion of a Powder Layer of Methane Hydrate: The Influence of Layer Height and Air Velocity Above the Layer; Flow, Turbulence and Combustion; Vol. 109 - Misyura S. Ya. Sergey Yakovlevich; Donskoy I. G. Igor Gennadjevich; Manakov A. Yu. Andrey Yurjevich; Morozov V. S. Vladimir Sergeevich; Strizhak P. A. Pavel Alexandrovich; Skiba S. S. Sergey Sergeevich; Sagidullin A. K. Aleksey Kausarovich (2022, 2022)
Title screen